Acute p‐synephrine ingestion increases fat oxidation rate during exercise - Gutiérrez‐Hellín, Jorge (Br J Clin Pharmacol, 2016)
AIMS: p‐Synephrine is a protoalkaloid widely used in dietary supplements for weight management because of its purported thermogenic effects. However, there is a lack of scientific information about its effectiveness to increase fat metabolism during exercise. The purpose of this investigation was to determine the effects of an acute ingestion of p‐synephrine on fat oxidation at rest and during exercise. METHODS: In a double‐blind, randomized and counterbalanced experimental design, 18 healthy subjects performed two acute experimental trials after the ingestion of p‐synephrine (3 mg kg(−1)) or after the ingestion of a placebo (cellulose). Energy expenditure and fat oxidation rates were measured by indirect calorimetry at rest and during a cycle ergometer ramp exercise test (increases of 25 W every 3 min) until volitional fatigue. RESULTS: In comparison with the placebo, the ingestion of p‐synephrine did not change energy consumption (1.6 ± 0.3 vs. 1.6 ± 0.3 kcal min(−1); P = 0.69) or fat oxidation rate at rest (0.08 ± 0.02 vs. 0.10 ± 0.04 g min(−1); P = 0.15). However, the intake of p‐synephrine moved the fat oxidation–exercise intensity curve upwards during the incremental exercise (P < 0.05) without affecting energy expenditure. Moreover, p‐synephrine increased maximal fat oxidation rate (0.29 ± 0.15 vs. 0.40 ± 0.18 g min(−1); P = 0.01) during exercise although it did not affect the intensity at which maximal fat oxidation was achieved (55.8 ± 7.7 vs. 56.7 ± 8.2% VO(2peak); P = 0.51). CONCLUSIONS: The acute ingestion of p‐synephrine increased the fat oxidation rate while it reduced the carbohydrate oxidation rate when exercising at low‐to‐moderate exercise intensities.